IMPLEMENTASI TOTAL QUALITY MANAGEMENT DALAM PENINGKATAN MUTU SEKOLAH - Erik Hadi Putra; Zulfani Sesmiarni; Darul Ilmi (at-Tahsin, 2024)
This research employs a qualitative method with a case study approach. Data collection involves observation, interviews, and documentation. The collected data are then descriptively analyzed using the data reduction, data presentation, and conclusion drawing process. Data validity is ensured through degrees of confidence and source/method triangulation. The results of the data analysis reveal several findings: (1) in the planning phase, it begins with the formation of the school development team (TPS), consisting of the school principal, vice principals such as curriculum vice principal, student affairs vice principal, public relations vice principal, infrastructure vice principal, administrative staff, senior teacher representatives, and the committee. They collectively formulate the school program in line with the school's vision and mission. (2) During the plan implementation stage, the majority of educators already use diverse teaching methods and media based on the lesson plans created at the beginning of the academic year. However, there are still some educators using conventional teaching methods. (3) In the evaluation stage, at the beginning of the new academic year, the school conducts a general opinion hearing (DPU) to review and evaluate the school's activities over the past year. Learning evaluation is carried out through daily assessments, mid-semester assessments (PTS), and end-of-semester assessments (PAS). (4) In the follow-up stage, the results show that the output of students from SMA Negeri 4 Bukittinggi is competitive enough for preferred higher education institutions such as UGM, ITB, UI, IPB, ITS, Undip, Unnes, UNY, UNJ, UIN, and state institutions like STAN, STIS, STSN.